Agile Project Management Impacts Software Development Team Productivity - Rahman, Abdul; Indrajit, Eko; Unggul, Akhmad; Dazki, Erick (Sinkron : jurnal dan penelitian teknik informatika, 2024)
The agile nature of the software development sector calls for flexible and effective project management techniques. Agile Project Management (APM) is emerging as a significant method that supports team cooperation, iterative improvement, and flexibility. This paper looks at how agile project management might affect software development team output. This study investigates the primary Agile methodologies Scrum and their impact on team productivity by means of a thorough literature review and empirical analysis. A mixed-methods approach employs qualitative comments and quantitative measures to provide a comprehensive view of output changes. We examine several software development teams inside a mid-sized technology company over 12 months using a case study approach, comparing productivity measures before and after Agile practices, including team satisfaction, development pace, and code quality. Furthermore, team member surveys and interviews offer an understanding of the supposed advantages and difficulties of switching to Agile approaches. Teams showing more efficiency, improved communication, and better morale point to a notable rise in productivity. Notable improvements included improved adaptability to shifting project needs and a shorter time-to-market for software products. This paper offers an insightful analysis of Agile Project Management's ability to revolutionize software development processes, helping companies trying to improve project results. This study has consequences for managers and practitioners because it provides valuable instructions for implementing Agile approaches to achieve the best team performance. Future directions of study will include investigating the long-term effects of Agile methods and their relevance in various organizational settings.